Puta, Pistoleira, Dona de Cabaré: a espetacularidade do corpo-cavalo-travestido de Dona Rosinha Malandra no Templo de Rainha Bárbara Soeira e Toy Azaka. Icoaraci/Pa. - CARVALHO, Ana Claudia Moraes de (Universidade Federal do Pará, 2021)
Through winding lines of aerial thoughts conceived by a butterfly-writer, I write about the body-horse of Dona Rosinha Malandra, Umbandist Left Entity. Dona Rosinha incorporates in Rosa Luyara, a Saint's Mother who is a transsexual from the Belém’s periphery, which is the preponderant factor for the development of libertarians and crossroads epistemologies, of immoral nature, whose poetic crossings were experienced by the actress-researcher-bacante, in the affective crossroads of the Amazonian Umbanda. Based on the poetic image of the vulgar-butterfly, the methodology developed in this thesis was configured in a process involving sweet deaths for new transformed lives. Through an ethno-affective method. Pupas, hot vulvas, cocoons, self-estrangements in the understanding of the house-cosmos perfumed with snake perfumes, which is the central force of a body-horse-transvestite. Prostitute, Gunslinger, Cabaret Owner reveals mysteries, secrets of a malandra worldview belonging to a present time, for the social empowerment of a community. As an epistemological contribution to the academy, I develop the notion of body leaning, which is configured in an epistemo-methodological proposal of a body in the process of creation. A butterfly-thesis. This study is a feminist thesis, with transformative, transgressive and deliciously imoral content. The research aims to raise ardent butterfly flights, based on ethnocenological notions of Armindo Bião e Miguel Santa Brigida, in the images of Barchelard, in the imaginary of Durand and in the sensitive thought of Maffesoli to prepare the paths to be walked in an identity construction of gender, community and artistical epistemic freedom